Health Care Use by Older Adults With Acute Myeloid Leukemia at the End of Life - Wang, Rong (J Clin Oncol, 2017)
PURPOSE: Little is known about the patterns and predictors of the use of end-of-life health care among patients with acute myeloid leukemia (AML). End-of-life care is particularly relevant for older adults with AML because of their poor prognosis. METHODS: We performed a population-based, retrospective cohort study of patients with AML who were ≥ 66 years of age at diagnosis and diagnosed during the period from 1999 to 2011 and died before December 31, 2012. Medicare claims were used to assess patterns of hospice care and use of aggressive treatment. Predictors of these end points were evaluated using multivariable logistic regression analyses. RESULTS: In the overall cohort (N = 13,156), hospice care after AML diagnosis increased from 31.3% in 1999 to 56.4% in 2012, but the increase was primarily driven by late hospice enrollment that occurred in the last 7 days of life. Among the 5,847 patients who enrolled in hospice, 47.4% and 28.8% started their first hospice enrollment in the last 7 and 3 days of life, respectively. Among patients who transferred in and out of hospice care, 62% received transfusions outside hospice. Additionally, the use of chemotherapy within the last 14 days of life increased from 7.7% in 1999 to 18.8% in 2012. Patients who were male and nonwhite were less likely to enroll in hospice and more likely to receive chemotherapy or be admitted to intensive care units at the end of life. Conversely, older patients were less likely to receive chemotherapy or have intensive care unit admission at the end of life, and were more likely to enroll in hospice. CONCLUSION: End-of-life care for older patients with AML is suboptimal. Additional research is warranted to identify reasons for their low use of hospice services and strategies to enhance end-of-life care for these patients.